Thermogravimetric study and evolved gas analysis of new microalga using TGA-GC-MS - Mohammed, Isah Yakub; Abba, Zubainatu; Matias-Peralta, Hazel Monica; Abakr, Yousif Abdalla; Mohammad Fuzi, Siti Fatimah Zahrah (Springer-Verlag, 2018)
The growing concerns over the environmental challenges emanating from the use of fossil fuels continue to generate interest in finding competitive and sustainable alternatives. This study presents physicochemical characteristics, thermal decomposition profile and kinetics of a new Botryococcus sp. of microalga isolated from Endau-Rompin, Malaysia. The proximate and ultimate analyses were carried out using standard analytical techniques. Thermogravimetric study was conducted in nitrogen atmosphere using a thermogravimetric analyser coupled with gas chromatography-mass spectrometer. The result revealed that the feedstock has high volatile matter (86.74 wt%) and calorific value of 17.18 MJ/kg. The thermal decomposition of the alga sample proceeded via dehydration, decomposition of extractives, hemicellulose, other carbohydrates and lipid evaporation. The kinetics of the alga sample evaluated using a distributed activation energy model showed that the model sufficiently described the pyrolysis of the feedstock with activation energy of 52.72–159.16 kJ/mol. The chemical composition of the evolved gas revealed high content of hydrocarbons, products of carbohydrate and protein decomposition. This suggests that the alga sample is a good candidate for production of valuable precursors for biofuel processing and production of biochemicals.